The contributions of Maternal Sensitivity and Maternal Depressive Symptoms to Epigenetic Processes and Neuroendocrine Functioning - Conradt, Elisabeth (Child Dev, 2016)
This study tested whether maternal responsiveness may buffer the child to the effects of maternal depressive symptoms on DNA methylation of NR3C1, 11β-HSD2, and neuroendocrine functioning. DNA was derived from buccal epithelial cells and pre-stress cortisol was obtained from the saliva of 128 infants. Mothers with depressive symptoms who were more responsive and who engaged in more appropriate touch during face-to-face play had infants with less DNA methylation of NR3C1 and 11β-HSD2 compared to mothers with depressive symptoms who were also insensitive. The combination of exposure to maternal depressive symptoms and maternal sensitivity was related to the highest pre-stress cortisol levels whereas exposure to maternal depressive symptoms and maternal insensitivity was related to the lowest pre-stress cortisol levels.